Dual-template synthesis of Co(OH)2 with mesoporous nanowire structure and its application in supercapacitor - Xue, Tong (2013)
A novel ordered mesoporous Co(OH)2 nanowire structure has been successfully fabricated by a dual-template method utilizing porous anodic alumina (PAA) and lyotropic liquid crystal (LLC) through potentiostatic electrodeposition technique. The mesoporous ordered hexagonal structure with cylindrical channels in Co(OH)2 nanowires is confirmed by low-angle X-ray diffraction (XRD) and transmission electron microscopy (TEM). A capacitance of 993 F g−1 for the mesoporous Co(OH)2 nanowire array is obtained from charge/discharge measurement at current density of 1 A g−1, indicating that the unique mesoporous nanowire structure can enhance its electrochemical properties.